PENDIDIKAN AGAMA ISLAM DI DESA OU KECAMATAN RIO VAKAVA KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Suharnis; Pengeran, Ismail (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2022)
This research aims to explain the views of the community in OU Village regarding Islamic religious education. This research uses qualitative methods with a phenomenological approach. The data sources used in this research consist of two data sources, namely primary data sources and secondary data sources. From the data that has been collected, the research results show that the people in OU Village, who generally come from the Tado tribe, have a view of Islamic religious education as a process of instilling good values originating from Islamic teachings such as personality formation and discipline in children. It is also a motivation for parents to prepare Islamic religious education for their children from an early age because children are a trust that must be looked after. Parents must prepare Islamic religious education as early as possible to protect them